The Chi-Square test: a frequency data based statistical device - Kumar, Ashok (Journal of Universal College of Medical Sciences, 2015)
“Cause Effect” relationships are very important and play a most vital and significant role in medical researchers to reveal efficacy of medication as preventive and curative measures towards control and eradication of various diseases and morbidity factors. The present paper, in this direction is an attempt to highlight the main applicability of - test ( chi- square test ) ; a most appropriate statistical device in testing statistical significance of the above mentioned relationships in studying impact of one on the other ; supplemented by a few citations thereof.